The next lap. - Lee, Jamie Wan Ling. (2009)
The “Next Lap” is a comprehensive 16-page tabloid comprising four sections that examines the efforts in developing young sportsmen here. It is a timely report with Singapore hosting the inaugural 2010 Youth Olympic Games for athletes aged between 14 and 18 and as the government turns to sports to build a diversified economy and inculcate patriotism. Through interviews with more than 60 people, we track the Singapore Sports School's challenges in the four years since it was established; the ties between the national sports associations and schools; and ask Singaporeans what it would take for them to embrace sports. We conclude that while Singapore is still not completely committed to producing champions, there has already been a shift in mindset.